Genome sequence of Erwinia amylovora bacteriophage Omen - Abreu, Gabriel Ferreira (2024)
We report the genome of Erwinia amylovora phage Omen, isolated from a Portuguese orchard. Omen has a genome size of 85,304 bp, belongs to the genus Kolesnikvirus (myovirus morphotype), and shares over 80% nucleotide identity with various Erwinia phage genomes.